Occupational causes of laryngeal cancer. Issue 2 (June 1984) - Olsen, J; Sabroe, S
Abstract : In a case-control study of all new cases of laryngeal cancer in Denmark from 1980 to 1982, 326 cases and 1134 community selected controls participated. Questionnaires were used to obtain information on education, occupation, and number of occupational exposures as well as smoking and drinking habits. High risk ratios for laryngeal cancer were found for semiskilled and unskilled workers, workers exposed to dust, out of doors workers, drivers, and people working in the cement industries and port services. The study hypothesis was that exposure to chromium or nickel increases the incidence rate of laryngeal cancer. No support for this was found concerning chromium, but exposure to nickel had a statistically significant risk ratio of 1.7.